Kawitā akawitā cintana - Nūra, Sutindara Siṅgha. (Cetanā Prakāshana, 2003)
Articles on modern Panjabi poetry.
Includes bibliographical references (p. 156).
Articles on modern Panjabi poetry.
In Panjabi.
Keywords: Panjabi poetry / 20th century / History and criticism. / http://id.loc.gov/authorities/subjects/sh2008108865